2013
DOI: 10.1212/wnl.0b013e3182a841e4
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus in oral shedding of children with multiple sclerosis

Abstract: Children with MS demonstrate abnormally increased rates of EBV viral reactivation and a broader range of genetic variants, suggesting a selective impairment in their immunologic control of EBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 35 publications
3
42
0
5
Order By: Relevance
“…Prior EBV infection is thus far the strongest and most consistent environmental factor associated with pediatric and adult‐onset MS 9, 10, 11, 12, 13, 20, 21. We observed that this association with pediatric MS is seen regardless of race and ethnicity, although the association is stronger in whites, as recently reported in adult‐onset MS 14.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Prior EBV infection is thus far the strongest and most consistent environmental factor associated with pediatric and adult‐onset MS 9, 10, 11, 12, 13, 20, 21. We observed that this association with pediatric MS is seen regardless of race and ethnicity, although the association is stronger in whites, as recently reported in adult‐onset MS 14.…”
Section: Discussionsupporting
confidence: 82%
“…Although several other studies investigated the association of prior viral infections and pediatric MS risk,9, 10, 11, 12, 13 very few studies examining the risk of MS in relation to previous viral exposures and the possible interactions with age, race and ethnicity have been conducted 14. Using a large case–control study, we aimed to assess the heterogeneity of association between remote infections with common herpesviruses and the risk of pediatric MS in children with a diverse racial and ethnic background.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the consensus sequence deriving from deep sequencing coincided with the one determined by Sanger sequencing, confirming the cosegregation of newly identified variants with the known EBNA2 alleles. We also found one or more variable positions in all HDs (1-17) and individuals with MS (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). For all couples of variants lying on the same read (coverage $50), the hypothesis of independent segregation, indicative of random sequencing errors, was rejected through a x 2 test (p , 0.05), thus supporting the coexistence of different genotypes.…”
Section: Resultsmentioning
confidence: 67%
“…7 To disclose possible MS-related EBV strains, various groups have followed a candidate-gene approach. [8][9][10][11][12][13][14] Along the same line, we chose to investigate EBV variability in MS by studying Epstein-Barr nuclear antigen 2 (EBNA2). EBNA2 is, in principle, the best candidate for this kind of study because it is the most polymorphic among all EBV genes: 5 major alleles of the EBV type 1 strain, the most frequent strain in the general Caucasian population, 15 have been identified based on nucleotide variations within the most variable region of EBNA2, which is also involved in the interaction with host proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation